Collection, storage, inspection and quality control of platelet concentrates obtained by apheresis: The situation in Spain. Issue 3 (June 2017) - Castrillo, Azucena; Jimenez-Marco, Teresa; Arroyo, José L.; Jurado, María L.; Larrea, Luis; Maymo, Rosa M.; Monge, Jorge; Muñoz, Carmen; Pajares, Ángel; Yáñez, Marta; ,
Abstract: Background: Diverse variables are involved in apheresis platelet collection, processing and storage. This survey shows how these are realized in Spain. Method: An analysis of collected data was performed in a questionnaire completed by ten Transfusion Centers (TC) which perform between 50 and 520 apheresis procedures per month. This information comprises the procedures used to collect, inspect and store apheresis platelet concentrates (PC), and quality control data. Results: Macroscopic inspection of PC is performed in all TC, especially during the first few hours post-collection and before distribution. The type of processor, duration of post-collection resting periods and temperature from the time of collection until distribution are similar in all TC. In 80% of TC, PC with small and scarce aggregates are distributed to transfusion services. The presence of clumps is influenced by type of processor, female donor, cold ambient temperature and collection of hyperconcentrated platelets, and is often recurrent in the same donor, although some TC have not found any influential variables. Overall, no objective inspection methods are followed, although there are exceptions. The degree of compliance with quality control parameters, such as the number of units studied, mean platelet yield, residual leukocyte counts and pH at expiry date, is acceptable in all TC. Compliance in terms of number of microbiological culture samples is variable. Discussion: The usual practice in Spanish TC with respect to the collection, post-collection handling and storage of apheresis PC can be considered uniform, although some specific aspects of analyses should follow more objective methods.